Construction and Characterization of a Mirror‐Image l‐DNA i‐Motif. (3rd January 2020) - Sun, Yawei; Yang, Bo; Hua, Yi; Dong, Yuanchen; Ye, Jianhan; Wang, Jiqian; Xu, Lijin; Liu, Dongsheng
Abstract: The first thermally stable and pH‐responsive quadruplex intercalated motif (i‐motif) structure formed by l ‐DNA is presented. Although this l ‐type i‐motif exhibits the same physiochemical properties as its d isomer, its inverted chirality and good enzymatic resistance potentially open the way to the development of new DNA materials of pharmaceutical and biological interest. Abstract : Through the looking glass : l ‐Type i‐motif DNA give the same performance as the corresponding natural DNA in terms of thermodynamic properties, but exhibited mirror‐image chirality and strong enzymatic resistance, potentially opening the way to the development of new DNA materials of pharmaceutical and biological interest.